Teratomas Mediastinal Recurrent with Massive Pericardial Effusion - Lilik Lestari; Muhammad Harris Sis Sultansyah (Universitas Muhammadiyah Semarang, 2023)
Background: Mediastinal teratoma is a medical rare disease that refers to the presence of a regrowing teratoma tumor in the mediastinum. At the pulmonary hospital dr. Ario Wirawan Salatiga, only one case was found, where the patient had previously been operated on at another hospital.Objective: The purpose of this paper was to contribute to the radiology literature by presenting a case of recurrent teratoma.Case Presentation: A 19-year-old male patient complained of persistent shortness of breath. The patient previously underwent teratoma surgery. The patient underwent chest X-rays, CT scans, abdominal and cardiac ultrasounds (USG), and as well as biopsies. The results of the CT scan found a teratoma-type mediastinal tumor accompanied by a large amount of pericardial effusion. A hyperechoic lesion with well-defined borders, round-oval, lobulated, and very large in size. Location in the mediastinum that is urgent and involves the left ventricle, right ventricle, left atrium, and right atrium. There is also an aortic compression lesion accompanied by calcification (+). Examination by ultrasonography (USG) of the heart found many pericardial but not found pressing. Heart valve function in patients did not show any abnormalities.Conclusion: Recurrent teratomas with large-volume pericardial effusions are rare. In this case study, a teratoma is located in the mediastinum. In this case, axial, coronal, and sagittal slices of a contrast thoracic CT scan can be used to establish the diagnosis. The results of heart USG found a pericardial effusion, the heart chambers do not collapse in this case of recurrent teratomas, indicating a mature teratoma type.